Evaluation of HRP2 and pLDH-based rapid diagnostic tests for malaria and prevalence of pfhrp2/3 deletions in Aweil, South Sudan - Emily Lynch; Tomas O. Jensen; Bachir Assao; Menard Chihana; Thadeous Turuho; Dan Nyehangane; John B. Manyok; Harriet Pasquale; Nimol Khim; Benoit Witkowski; Matthew E. Coldiron (Malaria Journal, 2022)
Abstract Background Rapid diagnostic tests (RDT) for malaria are the primary tool for malaria diagnosis in sub-Saharan Africa but the utility of the most commonly used histidine-rich protein 2 (HRP2) antigen-based tests is limited in high transmission settings due to the long duration of positivity after successful malaria treatment. HRP2 tests are also threatened by the emergence of Plasmodium that do not carry pfhrp2 or pfhrp 3 genes. Plasmodium lactate dehydrogenase (pLDH)-based tests are promising alternatives, but less available. This study assessed the performances of HRP2 and pLDH(pan) tests under field conditions. Methods The study performed a prospective facility-based diagnostic evaluation of two malaria RDTs in Aweil, South Sudan, during the high transmission season. Capillary blood by fingerprick was collected from 800 children under 15 years of age with fever and no signs of severity. SD Bioline HRP2 and CareStart pLDH(pan) RDTs were performed in parallel, thick and thin smears for microscopy were examined, and dried blood was used for PCR testing. Results Using microscopy as the gold standard, the sensitivity of both tests was estimated at  > 99%, but the specificity of each was lower: 55.0% for the pLDH test and 61.7% for the HRP2 test. When using PCR as the gold standard, the sensitivity of both tests was lower than the values assessed using microscopy (97.0% for pLDH and 96.5% for HRP2), but the specificity increased (65.1% for pLDH and 72.9% for HRP2). Performance was similar across different production lots, sex, and age. Specificity of both the pLDH and HRP2 tests was significantly lower in children who reported taking a therapeutic course of anti-malarials in the 2 months prior to enrollment. The prevalence of pfhrp2/3 deletions in the study population was 0.6%. Conclusions The low specificity of the pLDH RDT in this setting confirms previous results and suggests a problem with this specific test. The prevalence of pfhrp2/3 deletions in the study area warrants continued monitoring and underscores the relevance of assessing deletion prevalence nationally. Improved malaria RDTs for high-transmission environments are needed.